Corporate governance and business performance: The moderating role of external audit quality - Wong, Seng Foong; Yuvaraj, Ganesan; Pitchay, Anwar Allah; Hasnah, Haron; Hendayani, Ratih (Penerbit UMP, 2019)
The purpose of this study is to investigate the relationship of corporate governance attributes, i.e. board size, age diversity, risk management committee and internal audit function with the,business performance of the organisation. In addition, this study also examines the role of external audit quality as a moderating effect in the relationship between corporate governance and business performance. The study adopted a quantitative approach and cross-sectional design where it used a sample of 120 listed companies in Malaysia for the year 2016. Data is collected based on secondary data which is annual report year 2016. The result shows board size and the existence of risk management committee are negatively significant related to business performance while the other variables such as age diversity and internal audit function do not have an impact on business performance. Unexpectedly, external audit quality does not play a moderating role in related corporate governance and business performance. The study contributes to the understanding of the relationship between corporate governance and business performance in the developing country. The paper also provides related insight for regulators, policymakers and investors of emerging markets such as Malaysia. The study is the pioneer to understand the relationship of the risk management committee to business performance and moderating effect of external audit quality.